The study of biology practicum model in institute of teacher education (ITE) - Paramitha Cahyani; Aloysius Duran Corebima; Siti Zubaidah; Susriyati Mahanal (LPMPP Universitas Negeri Yogyakarta, 2021)
Practicum activities are inseparable components in learning biology. This research aims at revealing variety of practicum models designed by lecturers and the factors that influence their decisions to implement particular practicum models in their biology learning in ITE. The research was conducted for two semesters, involving 72 lecturers in 6 ITEs in Jember and Malang, Indonesia. The data were collected using interview method and document analysis. The results of this research revealed that the practicum model commonly implemented by the respondents were cooking recipe based practice model. This research also revealed that the current practicum structure does not have much development or difference from the practicum structure found in the previous studies. Although this practicum model has several disadvantages, the cooking recipe based practice model results in relatively good achievement of biology learning outcomes.